The Power of Turkey Diplomacy in Transfer of Function of Hagia Sophia to be a Mosque - Hendra Maujana Saragih; Meinita Hasya Eka Wulandari; Sri Issundari (AJIS: Academic Journal of Islamic Studies, 2021)
This paper aims to explain how aggressive the Turkish movement is under Erdogan's leadership and the domination of the ambitious AKP in an effort to restore the glory of Islam and spread its spirit of struggle on Turkish soil amidst secularism that has deeply rooted itself to dominate every aspect of life there. The synergy between the two slowly led to rivalries between authoritarian secularism and democratic nationalism with a touch of moderate Islamic nuances and Neo-Ottomanism which prioritized the freedom and welfare of the people, as well as reviving the power of the Ottoman Empire in a region that had previously entered its expansion area. Erdogan's actions, influenced by his life background, finally realized diplomacy in the form of Islamization in the form of changing the function of Istanbul's holy building, the Hagia Sophia, into a mosque while strengthening Erdogan's influence and Turkey's position in the international political arena, thus changing the direction of domestic policy as well as Turkish foreign policy despite steps This is also considered a controversial one-sided decision and poses a potential threat to peace in one's own country.